Abdominal Streaching Exercise and Warm Compresses of Ginger Decoction Affect The Reduction of Primary Dysmenorrhea Pain - Nelyanti, Dian Apri (Poltekkes Kemenkes Semarang, 2024)
Background: Dysmenorrhea is lower abdominal pain due to blood discharge from the uterus that generally bothers young women. The impact of dysmenorrhea makes it difficult for young women to move. One way to overcome dysmenorrhea is with non-pharmacological methods of giving abdominal stretching exercises and warm compresses of ginger decoction. This study aims to determine the effect of abdominal stretching exercises and warm compresses of ginger decoction on reducing primary dysmenorrhea pain in adolescent girls at SMA Negeri 1 Jamblang. Research method: Type of experimental quasi-research with two groups pre and post-test design. The population of adolescent girls in grade XI science and social studies who experience dysmenorrhea is 74 samples. Data were collected using questionnaire observation sheets with the Numeric Rating Scale pain scale, and bivariate analysis using the Wilcoxon test and the Friedman test. Results: The Friedman test obtained an average of dysmenorrhea pain after abdominal stretching exercise and warm compresses of ginger decoction in the intervention group and obtained an average post-treatment pain of 1.34. While in the control group given warm compress treatment ginger decoction obtained an average value of post-treatment pain of 1.66 with the highest decrease value on day 3 obtaining p value of 0.014 (p < 0.05). Conclusions and Suggestions: Giving abdominal stretching exercises and warm compresses of ginger decoction affects reducing the scale of primary dysmenorrhea pain in adolescent girls at SMA Negeri 1 Jamblang.